2018
DOI: 10.1007/s11121-018-0902-9
|View full text |Cite
|
Sign up to set email alerts
|

HIV Risk Among Displaced Adolescent Girls in Ethiopia: the Role of Gender Attitudes and Self-Esteem

Abstract: Adolescent girls in sub-Saharan Africa have been deemed one of the most critical populations to address in the campaign for an HIV-free generation. Experiences of intimate partner violence (IPV), harmful gender norms, diminished personal agency, and age-disparate sex have been identified as factors in the increasing rate of new infections among this population. Using baseline data from a cluster-randomized controlled trial in three refugee camps in Benishangul-Gumuz Regional State in Ethiopia, our study quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…11 Studies have verified that low self-esteem is associated with unhealthy behaviors and practices. For example, Ramiro et al 14 and Bermudez et al 15 reported that people with low self-esteem tend to engage in highrisk sexual behavior. Kima et al 16 also found that people with low self-esteem are more likely to experience mental health problems compared to people with high self-esteem.…”
Section: Introductionmentioning
confidence: 99%
“…11 Studies have verified that low self-esteem is associated with unhealthy behaviors and practices. For example, Ramiro et al 14 and Bermudez et al 15 reported that people with low self-esteem tend to engage in highrisk sexual behavior. Kima et al 16 also found that people with low self-esteem are more likely to experience mental health problems compared to people with high self-esteem.…”
Section: Introductionmentioning
confidence: 99%
“…The reason was that they wanted many children as this would be an advantage to them in terms of the food supply. This behaviour as well as transactional sex increases the risk of getting the virus, thereby preventing the achievement of healthy lives and the promotion of well-being for all ages (Bermudez et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, risk behavior performance differs between adolescents. Studies have shown that psychological constructs such as self-esteem and self-efficacy may help to understand why some adolescents are more inclined to the performance of risk behaviors than others (Bermúdez et al, 2019;Danielson et al, 2014;Louwet et al, 2018;Xu et al, 2017). This article focuses on the performance of sexual risk behaviors in adolescence, operationalized mainly as the inconsistent use of condoms.…”
Section: Seção: Artigomentioning
confidence: 99%